Clinical Trials Supporting the Role of the IL-17/IL-23 Axis in Axial Spondyloarthritis - Ceribelli, Angela; Motta, Francesca; Vecellio, Matteo; Isailovic, Natasa; Ciccia, Francesco; Selmi, Carlo (Frontiers in Immunology, 2021)
The term spondyloarthritis (SpA) encompasses a heterogeneous group of inflammatory musculoskeletal diseases with several common genetic background and clinical features, including the possible involvement of the axial skeleton with peripheral mono- or oligo- arthritis and frequently coexisting skin, eye and intestinal manifestations. When the sacroiliac joints or other parts of the spine or thoracic wall are predominantly affected at magnetic resonance or X-ray imaging with inflammatory back pain, the disease is classified as axial SpA and the therapeutic choices are significantly different compared to cases of peripheral arthritis. Moving from the narrow effectiveness and safety profiles of non-steroidal anti-inflammatory drugs, there has been a significant research effort aimed at identifying new treatments based on our better understanding of the pathogenesis of SpA. Indeed, in parallel with the solid data demonstrating that IL-17 and IL-23 are key cytokines in the development of enthesitis and spondylitis, monoclonal antibodies interfering with this pathway have been developed for the treatment of axial SpA. Furthermore, the IL-17/IL-23 axis is key to extra-articular manifestations such as inflammatory bowel disease, uveitis, and psoriasis which are frequent comorbidities of SpA. Currently available drugs act through these mechanisms recognizing IL-23 and targeting IL-17, such as secukinumab and ixekizumab. These therapeutic approaches are now envisioned in the international treatment recommendations for psoriatic arthritis with an axial phenotype as well as for ankylosing spondylitis. We will provide a concise comprehensive overview of the clinical evidence supporting the use of these and other drugs acting on IL-23 and IL-17 in axial SpA